Vitamin D Levels in Takayasu's Arteritis and a Review of the Literature on Vasculitides - (:unkn) unknown (WILEY, 2016)
Objective: Takayasu's arteritis (TAK) is a chronic, large-vessel vasculitis. Vitamin D, as a steroidal hormone, has recently been shown to have immunoregulatory and immunosuppressive effects. Low vitamin D levels are demonstrated in various autoimmune disorders. The aim of this study is to investigate vitamin D levels in patients with TAK. A comprehensive review of vitamin D levels in systemic vasculitides (SVs) is also performed. Methods: The study included 36 patients with TAK, 28 patients with Behc, et's disease (BD) as disease control and 30 sex-matched healthy controls. Plasma 25-hydroxy vitamin D (25(OH) vit D) levels were measured with high-performance liquid chromatography. Deficiency was defined as 25(OH) vit D levels below 25 nmol/l and insufficiency as below 50 nmol/l. Results: Plasma 25(OH) vit D levels were significantly lower in TAK patients (16.93 +/- 10.62 nmol/l) than healthy controls (64.63 +/- 21.82 nmol/l). Vitamin D level in BD patients (38.8 +/- 20.9 nmol/l) is lower than healthy controls but higher than TAK patients. The frequency of vitamin D deficiency was 83.3% in patients with TAK compared to 3.3% in healthy controls. Plasma 25(OH) vit D levels were same between clinically active and inactive patients. In literature review, very few studies were found to investigate vitamin D in SVs. Conclusion: We observed a high prevalence of vitamin D deficiency in patients with TAK. As various immune effects of vitamin D on mononuclear cells and arterial endothelium is shown, vitamin D deficiency can be a predisposing factor for immune activation in SV. We therefore suggest monitorization and replacement of vitamin D status in all TAK and other SV patients. (C) 2015 Wiley Periodicals, Inc.
Keywords: Takayasu's arteritis; vitamin D deficiency; vasculitis; BEHCETS-DISEASE; D DEFICIENCY; 1-ALPHA,25-DIHYDROXYVITAMIN D-3; AUTOIMMUNE-DISEASES; T-CELLS; SUSCEPTIBILITY; PATHOGENESIS; EXPRESSION; 1,25-DIHYDROXYVITAMIN-D3; POLYMORPHISMS